(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2025)
Calculating the distance of a star from Earth using stellar parallax makes sense only in two cases. In the first case, this is possible if the object we are observing is stationary in relation to the Sun, and in the second case, if the measurements are made simultaneously, but from two different locations. We will consider the case when the star moves uniformly with respect to the Sun. By measuring the Doppler effect at three different points, we will be able to determine the speed of light emitted from the star in the direction of the observer, the velocities at which the star and Sun move regarding the referential coordinate system and finally we will calculate the distance between the star and the observer.